Bounce of a golf ball on the green - Cross, R. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
A ball incident on a horizontal surface with backspin can rebound forwards or backwards depending on the angle of incidence and the amount of backspin. The ball can also bounce forwards several times before it bounces backwards. The outcome depends on whether the ball slides throughout the impact or whether the ball grips the surface during the impact. The physics of the bounce of a golf ball on a green is described in the present article and estimates are given of the stopping distance after the ball first lands on the green, based on experimental bounce data.